Maximizing Light Petroleum Gases (LPG) Yield From Atmospheric Distiller Of Crude Oil Distillation Using Response Surface Methodology - Kandasamy, Vinodini (Universiti Sains Malaysia, 2018)
Light petroleum gas (LPG) is a product of extruded oil ADU. LPG stands from refinery hydrocarbon gases such as methane, ethane, propane, butane and their existing isomers, used for various application worldwide. With the development of simulating software such as Aspen Plus and Design Expert, it is possible to simulate and optimize a specified process with desired end-product characteristics prior to plant running. As the LPG demand market grows tremendously worldwide, it is of utmost importance for LPG demand to be met. In this work, Aspen Plus is used to simulate and Design Expert is used to optimize an atmospheric distiller processing extruded crude into LPG and many more products. Simulation of the atmospheric distillation was done using a PETROFRAC distiller, crude assay 53016 beside operating parameters and inlet streams’ properties. Sensitivity analysis on the same PETROFRAC distiller model shows that three chosen operating parameters : furnace temperature, number of stages and ADU steam to feed ratio had significant effects on LPG yield. The LPG yield is found to be decreasing with increasing furnace temperature, number of stages and steam to feed ratio after a maximum value. The optimization study conducted in Design Expert software resulted in maximum LPG yield of 5.177% and throughput of 26.2 kg/s LPG for simulation model fed with 507 kg/s of crude at optimum process conditions : 603.15K furnace temperature, 33 number of stages and 1.90% of steam to feed ratio. The optimized yield, 5.177% achieved was higher than common LPG yield in industry which is 2.9%.